Yugto a rehabilitative juvenile reformatory center for the youth - Jalata, Chelsy Mae; Del Castillo, Nicolo Precioso (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
The foundation of a nation begins with the education of the children since they are considered one of its most important assets. However, because of many different factors, poverty being the number one case, the number of youth offenders in the society continue to rise. Children in Conflict with the Law who are awaiting court disposition of their cases are brought to halfway houses called Bahay Pag-asa that provide short-term residential care for the children for their rehabilitation. But most of theses BPAs threaten the welfare of the children instead of rehabilitating them. In Angeles City, 219 CICLs were recorded on 2016 but the city still has no BPA. In response, this book aimed to design a rehabilitative BPA in Angeles City. A rehabilitative BPA provides spaces for skill development, leisure and recreation, and comfortable accommodation of the CICL . Activities such as in workshop spaces were determined with consideration to the locality's available resources. It also utlized the green environment and building technologies that allows natural lighting and ventilation to minimize building operation costs. It also integrated theories like nature-based therapy and multisystematic therapy. Reformatory concepts such as in the layout of rooms, colors of classrooms, site boundary, softscapes and other factors were taken into account to help alleviate the atmosphere of the facility.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Children in Conflict with the Law; Children rehabilitation center -- Design